2005
DOI: 10.1111/j.1349-7006.2005.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐sized fluorescent particles as new tracers for sentinel node detection: Experimental model for decision of appropriate size and wavelength

Abstract: The concepts of made-to-order and low-invasiveness medicines are becoming widely accepted. A treatment for cancer, with minimum invasive surgery and without lymph nodes dissection based on sentinel lymph node (SN) navigation surgery, would adhere to these concepts. Dyes and/or radioisotopes are employed for SN detection in standard methods, however, each detection method has advantages and disadvantages. To make up for the disadvantages, we aimed at developing a new non-invasive method using fluorescent beads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 11 publications
(16 reference statements)
1
48
0
Order By: Relevance
“…This was not surprising as small molecule fluorophores are known drain to lymph nodes within minutes42, and previous studies of intratumoral injection of methylene blue revealed rapid drainage kinetics43. Larger nanoparticles (100–200 nm) can be used to significantly slow down the rate of drainage on the order of hours rather than minutes44. Sulforhodamine B–PoP-liposomes fall in this size range and were formed with self-quenching concentrations of the fluorophore.…”
Section: Resultsmentioning
confidence: 90%
“…This was not surprising as small molecule fluorophores are known drain to lymph nodes within minutes42, and previous studies of intratumoral injection of methylene blue revealed rapid drainage kinetics43. Larger nanoparticles (100–200 nm) can be used to significantly slow down the rate of drainage on the order of hours rather than minutes44. Sulforhodamine B–PoP-liposomes fall in this size range and were formed with self-quenching concentrations of the fluorophore.…”
Section: Resultsmentioning
confidence: 90%
“…These results demonstrate that the optical properties of L Ru are retained well in the NCPs. The red emission of the NCPs dominates in the biological transparent window; 19 the obvious advantage is avoiding and circumventing the disturbance from auto-fluorescence and scattering light of tissue to realize low-background imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Single fluorescent nanodiamond Low-photobleaching labeling agent [181] Perfluorocarbon MRI contrast agent for fibrin clots [184] Fluorescent polystyrene nanobeads Visualizing SLN [183] Carbon nanotubes (CNTs) Protein detection, [195] antigen and DNA detection [225] Si nanowires Streptavidin detection [193] Besides iron oxides, there are many other nanoscale materials being studied for medical imaging purposes. Gold nanocages as contrast enhancement agents for both optical coherence tomography and photoacoustic tomography showed an improved performance since the localized surface plasmon resonance of the Au nanocages can be tuned into the near-infrared (where the attenuation of light by blood and soft tissue is greatly reduced).…”
Section: Other Nanomaterialsmentioning
confidence: 99%
“…In another study, Nakajima et al used fluorescent polystyrene nanobeads with uniform sizes to efficiently visualize SLN by a laser scanning fluorescence detection system and determined the most appropriate size for SLN imaging in rats was 40 nm. [183] Conjugation with specific functional groups makes nanomaterials more promising for imaging purposes. For example, lipid-encapsulated perfluorocarbon nanoparticles were surface-modified by numerous Gd-diethylenetriaminepentaacetic acid (Gd-DTPA, a type of contrast agent) complexes to yield an effective targeted contrast agent for MRI-detection of fibrin clots, showing a dramatic increase in the detectability of fibrin clots compared to the test without using targeted contrast agents.…”
Section: Other Nanomaterialsmentioning
confidence: 99%